Preparing athletes and teams for the Olympic Games: Experiences and lessons learned from the world's best sport psychologists - Arnold, R.; Sarkar, M. (International Journal of Sport and Exercise Psychology, 2015)
As part of an increased effort to understand the most effective ways to psychologically prepare athletes and teams for Olympic competition, a number of sport psychology consultants have offered best-practice insights into working in this context. These individual reports have typically comprised anecdotal reflections of working with particular sports or countries; therefore, a more holistic approach is needed so that developing practitioners can have access to - and utilise - a comprehensive evidence-base. The purpose of this paper is to provide a panel-type article, which offers lessons and advice for the next generation of aspiring practitioners on preparing athletes and teams for the Olympic Games from some of the world's most recognised and experienced sport psychologists. The sample comprised 15 sport psychology practitioners who, collectively, have accumulated over 200 years of first-hand experience preparing athletes and/or teams from a range of nations for six summer and five winter Olympic Games. Interviews with the participants revealed 28 main themes and 5 categories: Olympic stressors, success and failure lessons, top tips for neophyte practitioners, differences within one's own consulting work, and multidisciplinary consulting. It is hoped that the findings of this study can help the next generation of sport psychologists better face the realities of Olympic consultancy and plan their own professional development so that, ultimately, their aspirations to be the world's best can become a reality.